Integration of technology acceptance model in the use of mobile banking among millennial generations of sharia bank customers in Indonesia - Zanuba Qothrun Nada; Joko Setyono (Fakultas Ekonomi dan Bisnis Islam UIN Salatiga, 2023)
This study explores the factors that influence the millennial generation in using Islamic bank mobile banking using the Technology Acceptance Model (TAM) approach by integrating external factors, namely religiosity and the role of trust as a mediating variable. The sample in this study was 185 respondents. Data analysis using Structural Equation Modeling - Partial Least Square (SEM-PLS). The test results show that of the seven direct effects tested, four relationships have a significant positive effect, namely perceived usefulness and trust in attitudes, as well as religiosity and attitudes towards intentions. While three relationships are not significant, namely, perceived ease of use and religiosity do not affect attitudes, and trust does not affect intentions. Furthermore, from the two indirect effects tested, there is a significant relationship: belief can mediate the relationship between religiosity and attitude.